2020
DOI: 10.24967/ekombis.v5i1.649
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Motivasi Kerja terhadap Kinerja Karyawan

Abstract: Motivasi kerja merupakan dorongan dasar yang menggerakkan seseorang atau keinginan untuk mencurahkan segala tenaga karena adanya suatu tujuan. Masalah kinerja menyebabkan penurunan suatu penjualan. Dengan adanya motivasi dan penilaian kinerja, tujuan organisasi dapat tercapai serta tercapai pula tujuan pribadi. Penelitian ini bertujuan untuk menganalisis pengaruh motivasi kerja terhadap kinerja karyawan pada plasza foto di Bandar Lampung. Penelitian ini menggunakan metode kuantitatif dengan analisis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…It can be indicated that work motivation influences performance because work motivation is an attitude or action that must be carried out by employees in complying with all applicable norms within the company, both written and unwritten, in order to achieve company goals optimally. The research results support the findings of previous researchers [15,16,17,18,20,21,22,24,25,26,27,28,29] that motivation has a significant effect on the performance of KPP Pratama South Sidoarjo employees. The results of this research do not support the findings [19,30,12] that motivation has no significant effect on employee performance.…”
Section: Data Reliabilitysupporting
confidence: 90%
See 2 more Smart Citations
“…It can be indicated that work motivation influences performance because work motivation is an attitude or action that must be carried out by employees in complying with all applicable norms within the company, both written and unwritten, in order to achieve company goals optimally. The research results support the findings of previous researchers [15,16,17,18,20,21,22,24,25,26,27,28,29] that motivation has a significant effect on the performance of KPP Pratama South Sidoarjo employees. The results of this research do not support the findings [19,30,12] that motivation has no significant effect on employee performance.…”
Section: Data Reliabilitysupporting
confidence: 90%
“…Motivation is a trigger from an individual that arouses the desire to carry out activities with the ability to achieve goals. Previous research results show that motivation has a significant effect on employee performance, including [15,16,17,18,19,20,21,22,23,11,24,25,26,27,28,29]. Different results were found [30,12] that motivation has no effect on employee performance.Job rotation reduces the level of boredom which causes an increase in employee motivation levels [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian milik Liliana (2021) memperjelas bila motivasi kerja memengaruhi substansial bagi kinerja karyawan PT Godrej Indonesia di Jakarta Timur. Demikian juga dengan karya ilmiah milik Fauziah (2020), mendapati bahwasanya motivasi kerja memengaruhi substansial bagi kinerja karyawan Plaza Foto di Bandar Lampung. Sama seperti penuturan FoEh, John E.H.J.…”
Section: Hasil Dan Pembahasan Motivasi Kerja Memengaruhi Kinerja Pegawaiunclassified
“…penelitian ini telah dilakukan sebelumnya yaitu motivasi kerja mempunyai pengaruh atas performance karyawan. Berdasarkan pada penelitian yang dilakukan oleh (Falah & Ayuningtias, 2020), (Fauziah et al, 2020) menunjukkan jika motivasi kerja mempunyai pengaruh yang positif dan signifikan atas performance karyawan, yang mana ini mempunyai arti jika semakin tinggi motivasi karyawan maka performance yang dimiliki akan semakin tinggi.…”
Section: Motivasi Kerja Karyawanunclassified